Patients with Autoimmune Thyroid Diseases Have Higher Prevalence of Positive Antiphospholipid Antibodies: A Systematic Review and Meta-Analysis - Difei Lu; Zhibo Song; Ying Gao; Junqing Zhang; Xiaohui Guo (International Journal of Endocrinology)
Introduction. Autoimmune thyroid diseases (AITDs) and antiphospholipid syndrome (APS) are commonly seen in childbearing-age women and can lead to recurrent miscarriages. Studies with a relatively small sample size were conducted and concluded inconsistent results on the relationship between AITDs and APS or the presence of antiphospholipid (aPL) antibodies. This meta-analysis aimed to provide evidence on the possible association between AITDs and APL using primary data from all relevant studies. Methods. Literature databases including PubMed, Embase, and Cochrane were searched from the time when the databases were established to March 2022. A total of 7 studies that met all inclusion criteria were selected in this meta-analysis, with 475 AITD patients and 764 healthy controls. After data extraction, the pooled odds ratio (OR) and the 95% confidence interval (95% CI) were calculated. Results. The risk of positive APL in AITD patients was approximately 3 folds higher in AITD patients compared with those in healthy controls (OR 3.41, 95% CI 2.29–5.08, p<0.001). There was no significant association between the risk of Graves’ disease (GD) and positive APL (OR 9.3, 95% CI 0.10–824.73, p=0.33). The risk of positive APL in patients with Hashimoto’s thyroiditis (HT) increased over 2 folds compared with healthy controls (OR 3.35, 95% CI 1.55–7.23, p=0.002). Conclusions. The result of this meta-analysis proved that the presence of APL was significantly increased in patients with AITD compared with healthy individuals, especially in patients with Hashimoto’s thyroiditis.